Development of Mechanized Hardware Description Language Signal Processing For Unmanned Aircraft System Applications - K. Sagar Vivek; SK. Farooq Abdulla; S. Pavan; P. Manikanta; G. Sudheer Kumar (International Journal of Scientific Research in Science and Technology, 2025)
Future Department of Defense needs include rapid implementation and testing of signal processing algorithms on forward deployed unmanned autonomous hardware systems. Various signal processing algorithms can be designed to test the feasibility of using MATLAB with the hardware description language (HDL) Coder toolbox for rapid implementation and their use in signal processing hardware for real time aerospace and missile applications. This documents the signal processing algorithms and test inputs, MATLAB implementation, and performance and implementation results for generated very high-speed integrated circuit hardware description language (VHDL) code for specific targets.
Keywords: signal processing; hardware description language; very high-speed integrated circuit hardware description language